2016
DOI: 10.1038/nmeth.3935
|View full text |Cite|
|
Sign up to set email alerts
|

A far-red fluorescent protein evolved from a cyanobacterial phycobiliprotein

Abstract: Far-red fluorescent proteins (FPs) are desirable for in vivo imaging because less light is scattered, absorbed, or reemitted by endogenous biomolecules. A new class of FP was developed from an allophycocyanin α-subunit (APCα). Native APC requires a lyase to incorporate phycocyanobilin. The evolved FP, named small Ultra-Red FP (smURFP), covalently attaches biliverdin (BV) without a lyase, and has 642/670 nm excitation/emission peaks, a large extinction coefficient (180,000 M−1cm−1) and quantum yield (18%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
226
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(238 citation statements)
references
References 41 publications
2
226
2
Order By: Relevance
“…3D). Meanwhile, it is reported that supplementation of Heme precursor, 5-aminolevulinic acid (ALA), and iron(ii) sulfate increases Biliverdin biosynthesis up to threefold (34). Contrary to our expectation, these treatments did not significantly increase PCB synthesis in either control HeLa or BVRA KO HeLa cells that expressed PHFF (Fig.…”
Section: Resultscontrasting
confidence: 83%
“…3D). Meanwhile, it is reported that supplementation of Heme precursor, 5-aminolevulinic acid (ALA), and iron(ii) sulfate increases Biliverdin biosynthesis up to threefold (34). Contrary to our expectation, these treatments did not significantly increase PCB synthesis in either control HeLa or BVRA KO HeLa cells that expressed PHFF (Fig.…”
Section: Resultscontrasting
confidence: 83%
“…Like BLI, light absorbance from hemoglobin is a problem, decreasing signal to noise ratio [2,68,85], hence fluorescent protein variants have been developed that emit at longer wavelength, with peak emission wavelength of 592nm, 635nm, 646nm and 675nm [86,–91]. Rodriguez et al developed a novel RFP from an allophycocyanin α-subunit (APCα), small ultra-red FP (smURFP), which covalently attaches a biliverdin (BV) chromophore without help from a lyase, and has a 670-nm excitation–emission peak [51]. Shu et al engineered IFP1.1, a bacterial phytochrome protein from Deinococcus radiodurans that incorporates biliverdin as the chromophore and fluoresces with peak emission at 708 nm that is well expressed in mammalian cells and in mice for whole-body imaging.…”
Section: Reporter Genes For Fluorescence Imagingmentioning
confidence: 99%
“…For example, the DMT1 reporter gene discussed in the MRI reporter gene section has been shown to be useful for tracking neural stem cells in a rat brain using a dual-modality PET and MRI manganese based imaging approach [55]. Another reporter gene that has been used in multimodal imaging is a triple fusion reporter consisting of firefly luciferase, a red or green fluorescent protein and a herpes simplex virus type 1 thymidine kinase (HSV1 TK), which allows one to track cell fate using bioluminescent, fluorescent, and PET imaging [51,5658]. Another previously mentioned reporter gene, hNIS, can be used for multimodal imaging using PET and Cerenkov Luminescence Imaging.…”
Section: Multimodal Imaging With Reporter Genesmentioning
confidence: 99%
“…Almost all of the genetically encoded fluorophores presently in use are derived from jellyfish (Aequorea victoria) or various corals (Discoma sp, Entacmacea quadricolor) 34,35 . These proteins native to aquatic invertebrates did not evolve to maximize their molecular brightness or photostability upon laser illumination in mammalian tissue, and thus all of the useful genetically encoded fluorophores have required much in vitro selection and optimization to make them more useful.…”
Section: Tools For Intravital Multi-photon Imaging Of Immune Responsesmentioning
confidence: 99%